The Effects of Cyberloafing in Indonesian Public Sector Workplaces: Analysis of Self-Regulatory Mechanisms and Anticipated Cost on Taking Charge Behavior - Desy Mayasari; Putriesti Mandasari (Jurnal Kawistara, 2026)
Cyberloafing, or non-work-related internet activities, has been associated with taking charge behavior that reduce employees’ work performance. This study examines how cyberloafing and anticipated cost relate to employees’ taking charge behavior in the workplace. Rather than treating these variables as inherently opposing influences, the study conceptualizes them as distinct forms of self-regulatory responses to workplace demands. Data were collected from 240 employees in Indonesia’s public sector, with an average age of 46 years and an average tenure of 18.7 years, representing a mature and experienced workforce. The findings show that cyberloafing is negatively associated with taking charge behavior, suggesting that frequent engagement in non-work-related internet activities may reduce employees’ capacity or willingness to initiate constructive changes. In contrast, anticipated cost is positively related to taking charge, indicating that employees who are more attentive to potential risks may also be more deliberate and prepared when engaging in proactive efforts. These results suggest that proactive behavior is shaped not only by tendencies toward disengagement but also by individuals’ evaluation of potential consequences. By integrating these perspectives, the study offers a more balanced understanding of how employees regulate their behavior under dynamic work conditions. It highlights the coexistence of avoidance-oriented and evaluative processes in shaping proactive action. From a practical standpoint, the findings underscore the importance of managing cyberloafing without suppressing employees’ capacity for recovery, while also fostering constructive awareness of risks to support more effective taking charge behavior. This study contributes to the literature by providing a nuanced account of employee behavior in Indonesia’s public sector, where such dynamics remain underexplored